Optimizing Seedling Density per Planting Hole of Lettuce (Lactuca sativa L. var. longifolia) in a Deep Flow Technique Hydroponic System - Febriana, I Gede; Wijana, Gede; Sukewijaya, I Made; Darmawati, Ida Ayu Putri; Pradnyawathi, Ni Luh Made (Agro Bali : Agricultural Journal, 2025)
Market demand for baby romaine lettuce (Lactuca sativa L. var. longifolia) continues to rise alongside the public’s growing preference for healthy lifestyles, yet its productivity still needs improvement. This study aims to evaluate the effect of seedling density per planting hole on the growth and yield of baby romaine lettuce using the Deep Flow Technique (DFT) hydroponic system and to determine the optimal number of seedlings. The experiment was conducted in a greenhouse in Pelaga Village, Bali, using a completely randomized design (CRD) with a single factor comprising five seedling densities (1, 2, 3, 4, and 5 seedlings per hole) and six replications, totaling 120 plants.  Growth and yield parameters were analyzed using ANOVA and LSD at a 5% significance level, with regression applied to fresh shoot and crop weight. Results showed that increasing the number of seedlings significantly affected plant height, stem diameter, chlorophyll content, fresh and dry shoot weight, and total fresh biomass. Shoot fresh weight increased linearly (Y = 97.86 + 11.71X; R² = 0.975), while crop fresh weight followed a quadratic trend (Y = 70.64 + 8.10X – 1.00X²; R² = 0.863), with the optimal yield obtained at three seedlings per hole. It is concluded that planting three seedlings per hole offers the best outcome in terms of both quality and quantity in a DFT hydroponic system.